Policy Analysis on The Removal of Age Limits in Indonesian Labor Recruitment: A Public Policy Perspective - Rivany, Deaotna; Supriyatno, Budi; Hakim, Azis (Dinasti International Journal of Management Science, 2026)
The removal of age limits in recruitment processes is a vital issue in achieving justice and equal opportunity for all citizens. Although the government has not yet issued a formal regulation explicitly abolishing age limits, several non-regulatory policy instruments, including the Circular Letter of the Minister of Manpower of the Republic of Indonesia Number M/06/HK.04/V/2025 concerning the Prohibition of Discrimination in the Labor Recruitment Process, indicate a policy shift toward more inclusive recruitment practices. This study aims to analyze the dynamics of the policy to abolish age limits from a public policy perspective, including agenda setting, policy instruments, and public readiness for its implementation. The research uses a qualitative descriptive approach with document analysis and public policy theory. The results show that the policy of abolishing age limits is currently at the "soft policy" stage, but it holds great potential to drive behavioral changes among employers, increase public literacy, and strengthen the cross-age vocational training ecosystem. This study provides important implications for formulating more comprehensive policies, both in the form of legislation and labor competency improvement programs.